A comparative study of efficacy and safety of flupirtine versus piroxicamin patients with low back pain - Sharma, Ambrish; SM, Manjunath; G, Nagesh Raju; B, Dharmaraj; MR, Nagendra Gowda (International Journal of Research in Medical Sciences, 2017)
Background: Low back pain is a common musculoskeletal symptom caused by a variety of disorders that affect the lumbar spine. The most frustrating aspect in the treatment of low back pain is that there is “no magic bullets”. The objective of the study was to compare the efficacy and safety of flupirtine versus piroxicam in patients with back pain. Methods: This was prospective, open labeled, randomized, comparative clinical study conducted by the Departments Orthopedics and Pharmacology, BMC&H, Chitradurga. Study was conducted on 60 patients of either sex, aged above 18 years with low back pain. Assessments were done for Finger-to-Floor Distance (FFD), lumbar pain, Lasegue’s sign, tenderness of vertebral muscles, pain & sensory disturbance in lower limbs and response to therapy for efficacy. Parametric data was analyzed by t-test and proportions were compared using Chi-square test. Results: 74 patients were randomized to 2 groups of 37 each. Group I patients received flupirtine maleate 100 mg twice daily and Group II patients received piroxicam 20 mg twice daily for 14 days. 30 patients in each group completed the study and were analysed. On intergroup comparison, there was no statistical difference (p>0.05) in the efficacy parameters of finger-to-floor distance (FFD), lumbar pain, Lasegue’s sign, tenderness of vertebral muscles, sensory disturbance in lower limbs, VAS scores & global assessment of response to therapy. 13.3% in flupirtine group and 16.6% in piroxicam group reported adverse events. Conclusions: Both flupiritine and piroxicam were equally effective but flupirtine was better tolerated than piroxicam.